2009
DOI: 10.1007/s11096-009-9355-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in community pharmacy: a qualitative study of business models and cognitive services

Abstract: Active support and encouragement to transition from being dependent on dispensing to implementing services is needed. The study showed that pharmacies where services were implemented and showed success are those strategically differentiating their businesses to become focused health care providers. This holistic approach should inevitably influence the sustainability of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Some of the themes identified by Chui and her colleagues also resonate well with the results of work conducted in Australia by Roberts, Feletto and their colleagues [32][33][34][35][36].…”
Section: Organizational Flexibilitysupporting
confidence: 70%
See 3 more Smart Citations
“…Some of the themes identified by Chui and her colleagues also resonate well with the results of work conducted in Australia by Roberts, Feletto and their colleagues [32][33][34][35][36].…”
Section: Organizational Flexibilitysupporting
confidence: 70%
“…These eight themes were: (1) culture, (2) One area is based upon research conducted in the United States by Doucette and colleagues [31] in which they identified organizational factors that influence pharmacy practice change. The other area is based upon research conducted in Australia by Roberts, Feletto and colleagues [32][33][34][35][36] in which they used an organizational theory framework [37] to provide a greater understanding of change processes and their facilitators in community pharmacies.…”
Section: Work System Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall the core finding of this study was the potential for community pharmacies to move beyond medication supply and become a health hub destination that assisted consumers with chronic conditions across three key domains: health care system navigation, medication management and eventually, health advocacy. Although the shift for pharmacy to provide professional health services has been emphasised both nationally 30 and internationally, 7,31,32 the notion that they could provide consumer support to navigate the health system and act as health advocates broadens the patient-centred approach to care. Barriers associated with an extended health care role were also discussed and reinforce those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%